Epidemiology of early onset dementia and its clinical presentations in the province of Modena, Italy. Issue 1 (11th September 2020) - Chiari, Annalisa; Vinceti, Giulia; Adani, Giorgia; Tondelli, Manuela; Galli, Chiara; Fiondella, Luigi; Costa, Manuela; Molinari, Maria A.; Filippini, Tommaso; Zamboni, Giovanna; Vinceti, Marco
Abstract: Introduction: Patients with early onset dementia (EOD), defined as dementia with symptom onset at age <65, frequently present with atypical syndromes. However, the epidemiology of different EOD presentations, including variants of Alzheimer's disease (AD) and frontotemporal dementia (FTD), has never been investigated all together in a population‐based study. Epidemiologic data of all‐cause EOD are also scarce. Methods: We investigated EOD epidemiology by identifying patients with EOD seen in the extended network of dementia services of the Modena province, Northern Italy (≈700, 000 inhabitants) from 2006 to 2019. Results: In the population age 30 to 64, incidence was 13.2 per 100, 000/year, based on 160 new cases from January 2016 to June 2019, and prevalence 74.3 per 100, 000 on June 30, 2019. The most frequent phenotypes were the amnestic variant of AD and behavioral variant of FTD. Discussion: EOD affects a significant number of people. Amnestic AD is the most frequent clinical presentation in this understudied segment of the dementia population.